RFamide-related Peptide-3 and the Trade-off between Reproductive and Ingestive Behavior - Schneider, Jill E (Integr Comp Biol, 2017)
Ingestive and sex behaviors are important for individual survival and reproductive success, but when environmental energy availability is limited, individuals of many different species make a trade-off, forfeiting sex for ingestive behavior. For example, food-deprived female Syrian hamsters (Mesocricetus auratus) forego vaginal scent marking and lordosis (sex behaviors) in favor of foraging, hoarding, and eating food (ingestive behavior). Reproductive processes tend to be energetically costly, and individual survival requires homeostasis in metabolic energy. Thus, during energetic challenges, the chances of survival are enhanced by decreasing the energy expended on reproductive processes. The entire hypothalamic-pituitary-gonadal (HPG) system is inhibited by severe energetic challenges, but comparatively little is known about the effects of mild energetic challenges. We hypothesized that (1) a trade-off is made between sex and ingestive behavior even when the level of food restriction is insufficient to inhibit the HPG system; (2) mild energetic challenges force a trade-off between appetitive ingestive and sex behaviors, but not consummatory versions of the same behaviors; and (3) the trade-off is orchestrated by ovarian steroid modulation of RFamide-related peptide 3 (RFRP-3). In other species, RFRP-3, an ortholog of avian gonadotropin-inhibitory hormone, is implicated in control of behavior in response to energetic challenges and stressful stimuli. In support of our three hypotheses, there is a “dose-response” effect of food restriction and re-feeding on the activation of RFRP-3-immunoreactive cells in the dorsomedial hypothalamus and on appetitive behaviors (food hoarding and sexual motivation), but not on consummatory behaviors (food intake and lordosis), with no significant effect on circulating levels of estradiol or progesterone. The effect of food restriction on the activation of RFRP-3 cells is modulated at the time of estrus in gonadally-intact females and in ovariectomized females treated with progesterone alone or with estradiol plus progesterone. Intracerebral treatment with RFRP-3 results in significant decreases in sexual motivation and results in significant but small increases in food hoarding in hamsters fed ad libitum. These and other results are consistent with the idea that ovarian steroids and RFRP-3 are part of a system that orchestrates trade-offs in appetitive behaviors in environments where energy availability fluctuates.